Comparison of serum, ear notches, and nasal and saliva swabs for Bovine viral diarrhea virus antigen detection in colostrum-fed persistently infected (PI) calves and non-PI calves - Lanyon, Sasha R; Sims, Sarah K; Cockcroft, Peter D; Reichel, Michael P (Journal of veterinary diagnostic investigation, 2014)
The diagnosis of neonatal and young calves persistently infected (PI) with Bovine viral diarrhea virus (BVDV) by antigen-capture enzyme-linked immunosorbent assay (ACE) may be complicated by interference from colostrum-derived specific antibodies. Ten calves, with 3 calves identified as PI and 7 as non-PI were used in the current study. All non-PI calves were shown to be seropositive for BVDV-specific antibodies by antibody enzyme-linked immunosorbent assay (Ab-ELISA) on serum. Serum samples, ear notch samples, and nasal and saliva swabs were collected from each calf from birth until 12 weeks of age and tested by ELISA for BVDV-specific antigen and antibodies. Following colostrum ingestion, Ab-ELISA sample-to-positive (S/P) ratios rose by a mean of 0.95 (95% confidence interval [CI] = 0.64-1.25) and 1.72 (95% CI = 1.55-1.89) in seropositive, non-PI calves and in PI calves, respectively. The mean S/P ratios then declined to approximately 1.1 in non-PI calves and 0.5 in PI calves at between 60 and 80 days of age. In PI calves, testing for antigen in serum and nasal and saliva swabs was subject to interference by colostrum-derived antibodies in calves up to 3 weeks of age. Nasal swabs were less affected than serum and saliva swabs. Ear notches maintained positive ACE corrected optical densities at all sample times, despite a drop in the signal following the ingestion of colostrum.